The Effect of Vernacular Language on Ethnic Voting Patterns in Kenya: A Case of Kondele Ward, Kisumu County, Kenya - Lisege, Henry Otulo; Ochieng, Robert Onyango; Achieng, A. Lucy (Journal of African Interdisciplinary Studies, 2019)
Ethnic voting is often problematic for democratic accountability because it reduces the likelihood that poor-performing and corrupt politicians will be voted out of office. Further, it can generate instability and violence by exacerbating inter-group opposition and animosity. Traditional knowledge holds that ethnicity is a key determinant of voting behavior in an awful lot of the growing world and that many nations’ political woes are due, at least partially, to the politicization of ethnicity. This research sought to determine the impact of the use of vernacular language on ethnic voting pattern in Kenya, especially Kisumu County. The study sought to evaluate the factors that contributed to ethnic voting in Kondele ward, Kisumu County, to trace the trend of ethnic voting in Kondele ward, Kisumu County, to determine the relationship between vernacular language and ethnic voting in Kondele ward, Kisumu County. Kondele ward was reported to have the highest deaths during the 2017 elections unlike other Sub-Counties in Kisumu. A target population of 440 was used but a sample of 240 respondents comprising 200 local voters and 40 politicians was opted for. Simple random sampling was used to select 50% of the politicians and party members from the major coalitions. This study made use of primary data. The study collected primary data by use of questionnaires. Quantitative data was analyzed using Statistical Package for Social Sciences (SPSS) version 20. The descriptive statistics approach was adopted for analyzing and presenting the data in this research. The analyzed information was then presented in tables and figures. From the findings, it was identified that ethnic voting has led to election violence in many parts of the world, Kenya being a victim. Majority of the respondents positively concluded that indigenous languages greatly contributed to ethnic voting and this was stimulated by political activities. This study has given recommendations on how to prevent adverse effects of ethnic voting like election violence.
Keywords: Kenya; Kisumu County; Vernacular Language; Ethnic Voting Patterns; Kondele Ward